Pengaruh konsentrasi sari jeruk nipis (citrus aurantifolia) dan sari tebu (saccharum officinarum) terhadap ph, antioksidan, dan organoleptik seduhan bunga telang (Clitoria ternatea): Effect of lime (citrus aurantifolia) and sugar cane (saccharum officinarum) concentrations on ph, antioxidants, and organoleptik of telang flower (clitoria ternatea) - Utomo, Deny; Abidin, Mohammad Nurul (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Telang flower (Clitoria ternatea) is an antioxidant-rich flower that often grows in yards, forests, or even outside gardens. Butterfly pea flowers are rich in antioxidants and are better known as medicinal plants. This study aims to determine the effect of the concentration of lime juice and sugar cane juice. The research method used a factorial Randomized Block Design (RBD) with 2 treatment factors, namely the concentration of lime juice (1.5%, 2% and 2.5%) and sugarcane juice (60%, 65% and 70%). The variables studied included chemical parameters (pH value and antioxidant activity) and sensory parameters (taste, aroma and color). Data analysis for chemical parameters was analyzed using ANOVA statistics, followed by the Tukey test, while sensory parameters used the Friedman method. The best chemical and sensory analysis treatment uses the De Garmo Effectiveness Index method. The best treatment was combination 9, namely J3T3 (concentration of 2.5% lime juice and 70% of sugarcane juice) with chemical and organoleptic parameters including pH 3.53%, antioxidant activity 98.06 mg/ml, taste 3.84 (very like), aroma 2.80 (like), and color 2.16 (like).